Jurisdictional Overlap Between the Civil Courts and the Syariah Courts: Analysis and Solutions - Jamadi bin Saleh; Muhammad Mujiburrahman Amir Paisal; Nurul Rafeeqa Afdul Mutolip; Faezahwaty Abdul Mohamed Ibnu; Mervyn @ Hasan Sainy; Hairul Vaiyron bin Othman; Ritchie Jay Cheng; Mohd Zulfadhli Darman Shah; Asmidah Ahmad (Faculty of Syariah and Law, USIM, 2026)
Malaysia adopts a dual judicial system which separates the jurisdiction of the Civil Courts and the Syariah Courts as provided under the Federal Constitution. This division is primarily based on Article 121(1A) and the State List in the Ninth Schedule, which empowers the State Legislative Assemblies to enact laws relating to Islamic affairs. However, in practice, the separation is not without overlap, particularly in matters involving religious status, marriage and divorce, child custody, and Syariah criminal offences. Such overlap arises when the jurisdictional conditions of the Syariah Courts—namely that the parties must be Muslims and the subject matter must fall within Paragraph 1 of the State List—intersect or conflict with the jurisdiction of the Civil Courts. This has led the Courts, especially the Federal Court, to resolve interpretative conflicts through case law, as seen in Latifah bte Mat Zin, Indira Gandhi, Iki Putra Mubarrak and Nik Elin Zurina. This study examines the historical basis of the judicial division, clarifies the jurisdictional scope of both Courts, evaluates the issues of overlap that arise, and proposes recommendations for harmonising the judicial system to ensure clarity, coherence, and effective administration of justice in Malaysia’s plural society.